Aspectos clínicos e epidemiológicos de mulheres atendidas no ambulatório de climatério em unidade de referência. - CHAMIÉ, Rosana Ferreira Cunha (2023)
Purpose: to determine the profile epidemiologist and clinical aspects of women in the climateric. Methods: a description cross-sectional study of 200 women after menopause age between 40 and 60 years was carried out at the Climacterium Outpatient Clinic Fundação Santa Casa de Misericórdia do Pará (FSCM-PA) from May to August of 2011. Women with less had been excluded than 40 and more than 60 years of age and not acceptance in participating of the study. For the collection data structuralized questionnaire was used and previously tested. The data had been analyzed by test t Student, as well as the qui-square and accurate of Fischer. Resulted: the menopause occurred on average to the 44,57 years. Sexual activity was related by 69,2% of the interviewed ones, amongst these, 74,8% had after informed the occurrence of change in the sexual relation after the menopause, as loss of the libido, drying vaginal and dispareunia. In 55,3% of the cases the menopause occurred of spontaneous form; e in excessively, had the surgical procedure (Hysterectomy or Hysterectomy + Ooforectomy), in function of pelvic pathology of base, being the main uterine leiomyoma. 52.5% of the interviewed ones had alleged to be carrying through hormone therapy, due symptom (s) attributed to the climacteric, are they psychological and/or vasomotors. The used medication hormonal therapy sufficiently was diversified and had been few the cases of collateral effect. The majority of the patients carried through complementary examinations (Mammograms- 87,6%; Oncotic colpocitology- 100% and Transvaginal ulstrasonography- 88,6%) before the beginning of the accomplishment of the hormone therapy, as well as in the accompaniment of the therapy. Many interviewed had pathology associated with the climateric, being the main a Sistemic Arterial Hypertension presented for 27,5% of patients. But 27% had disclosed to exert physical activity and few had declared use 9 tobacco (7.5%) and/or use alcohol (17%). Conclusions: The climacteric is a continuous process of expansion due to the progressive aging of the population because of this the study presented here aimed to better conduct these patients focusing on their welfare. With the same focus of the clinic Santa Casa de Misericórdia do Pará showed enough competence to an approach to these patients about their symptoms, conduct, conducting laboratory tests to evaluate them, and the introduction of hormone therapy when necessary. Menopause is multifactorial phenomenon, including cultural due to be highly variable and complex.